2021
DOI: 10.3390/microorganisms9040871
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota Can Provide Viral Tolerance in the Honey Bee

Abstract: Adult honey bees host a remarkably consistent gut microbial community that is thought to benefit host health and provide protection against parasites and pathogens. Currently, however, we lack experimental evidence for the causal role of the gut microbiota in protecting the Western honey bees (Apis mellifera) against their viral pathogens. Here we set out to fill this knowledge gap by investigating how the gut microbiota modulates the virulence of a major honey bee viral pathogen, deformed wing virus (DWV). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…This study demonstrated that enhancing indigenous gut microbiota may decrease mortality but not control the pathogen, and somewhat similar results have been reported in a field trial [ 61 ]. In addition to nosema disease, other non-bacterial gut pathogens, i.e., trypanosomatids and DWV, also reported somewhat counter-intuitive results [ 38 , 70 ]. These pathogens seemed not affected by adding indigenous gut microbes, and the host mortalities were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that enhancing indigenous gut microbiota may decrease mortality but not control the pathogen, and somewhat similar results have been reported in a field trial [ 61 ]. In addition to nosema disease, other non-bacterial gut pathogens, i.e., trypanosomatids and DWV, also reported somewhat counter-intuitive results [ 38 , 70 ]. These pathogens seemed not affected by adding indigenous gut microbes, and the host mortalities were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the different levels of the two DWV variants observed were caused by venereal transmission, i.e., from differentially infected drones to their offspring. Additionally, differences in DWV genome copies may have also resulted from interactions with other microorganisms, such as pathogens [ 53 , 54 ] or the host’s gut microbiota [ 55 ]. Finally, differential resilience towards virus infection exhibited by the pupae subfamilies could explain these results [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota often help the host to defend against various pathogens (Lozupone et al ., 2012). In honeybees, gut microbiota confers viral tolerance, which means that normal gut microbiota can promote the fitness of DWV‐infected hosts without control of viral loads (Dosch et al ., 2021). More efforts should be devoted to further understanding the protective role of bumblebee gut microbiota against viral pathogens.…”
Section: Potential Roles Of the Gut Microbiota In Pathogen Resistancementioning
confidence: 99%